An innovative protein expression system using RNA polymerase I for large‐scale screening of high‐nucleic‐acid content Saccharomyces cerevisiae strains. Issue 6 (27th August 2020) - Zeng, Duwen; Qiu, Chenxi; Shen, Yu; Hou, Jin; Li, Zailu; Zhang, Jixiang; Liu, Shuai; Shang, Jianli; Qin, Wensheng; Xu, Lili; Bao, Xiaoming
Summary: Saccharomyces cerevisiae is the preferred source of RNA derivatives, which are widely used as supplements for foods and pharmaceuticals. As the most abundant RNAs, the ribosomal RNAs (rRNAs) transcribed by RNA polymerase I (Pol I) have no 5′ caps, thus cannot be translated to proteins. To screen high‐nucleic‐acid content yeasts more efficiently, a cap‐independent protein expression system mediated by Pol I has been designed and established to monitor the regulatory changes of rRNA synthesis by observing the variation in the reporter genes expression. The elements including Pol I‐recognized rDNA promoter, the internal ribosome entry site from cricket paralytic virus which can recruit ribosomes internally, reporter genes ( URA3 and yEGFP3 ), oligo‐dT and an rDNA terminator were ligated to a yeast episomal plasmid. This system based on the URA3 gene worked well by observing the growth phenotype and did not require the disruption of cap‐dependent initiation factors. The fluorescence intensity of strains expressing the yEGFP3 gene increased and drifted after mutagenesis. Combined with flow cytometry, cells with higher GFP level were sorted out. A strain showed 58% improvement in RNA content and exhibited no sequence alteration in the whole expression cassette introduced. This study provides a novel strategy for breeding high‐nucleic‐acid content yeasts. Abstract : By using the more effective IRES (internal ribosome entry site) element, an innovative cap‐independent protein expression system mediated by RNA polymerase I, which only transcribes rRNA normally, was established in Saccharomyces cerevisiae . Such system made the reporter gene yEGFP3 express variation especially after mutagenesis. Combined with flow cytometry, cells with high fluorescence intensity were sorted from 200, 000 cells and the strain with 58% RNA content higher than the parental strain was obtained. So the model for large‐scale screening of high‐nucleic‐acid content yeasts was set up.